α-Amylase and α-Glucosidase Inhibitory Activities of Phenolic Extracts from Eucalyptus grandis × E. urophylla Bark - Ping Jiang; Jia Xiong; Fei Wang; Mary H. Grace; Mary Ann Lila; Rui Xu (Journal of Chemistry)
This study evaluated the inhibitory effects of different extracts and fractions from Eucalyptus. grandis × urophylla bark (EB) against α-glucosidase and α-amylase enzyme activities. The ethyl acetate extract (EB-E) showed the highest activity among others. Seven fractions were derived from EB-E; among them EB-E-7 showed the highest significant inhibition of both enzymes, with IC50 of 1.40±0.18 and 1.72±0.12 μg/mL, respectively. EB-E and its active fraction EB-E-7 showed highest contents of total phenolics: 178.79±4.68 and 920.4±5.46 mg GAEag−1, respectively. HPLC-MS analysis of EB-E-7 revealed the presence of ellagic acid, quercetin-glucuronide, quercetin-3-α-rhamnopyranoside, and ellagic acid rhamnoside as major compounds, together with smaller concentrations of myricetin-rhamnoside, isorhamnetin-hexoside, myricetin-3-α-arabinofuranoside, and isorhamnetin. Therefore, the phenolic compounds from Eucalyptus grandis × E. urograndis bark potently inhibited α-amylase and α-glucosidase activity, having potential in prevention of hyperglycemia.